Efficacy of entomopathogenic fungi against Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) under laboratory conditions - Musso, Anahí (2020)
Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) is a primary insect pest of stored grains. The aim of this study was to evaluate the efficacy of 10 different isolates of entomopathogenic fungi as biocontrol agents against R. dominica. The chosen isolates were Beauveria bassiana CEP 545, CEP 560 and CEP 567, Metarhizium robertsii CEP 381 and CEP 401, M. anisopliae sensu lato CEP 615, CEP 616 and CEP 617 and Cordyceps (=Isaria) fumosorosea CEP 303 and CEP 309. Insects were sprayed with a conidial suspension of each fungus and incubated for 15 days under laboratory conditions. Insect mortality (expressed as percentage) and median survival times (MST) were estimated. Beauveria bassiana caused the highest mortality (47-65%), whereas the other fungal isolates caused a maximum mortality of 21%. The B. bassiana CEP 545 and CEP 567 isolates led to an MST of 8 and 9 days, respectively. Among all the isolates tested, B. bassiana CEP 545 was the most efficient as a biocontrol agent. The median lethal concentration (LC50) of this isolate was calculated with five concentrations on day 15 after the treatment. The insect mortality increased with the highest isolate concentrations and the LC50 was estimated in 9.54x109 conidia mL-1. This study confirmed that some B. bassiana isolates, especially CEP 545, could be used as biocontrol agents against R. dominica.